SPATIAL MODEL OF SUMATRAN TIGER (Panthera tigris sumatrae) POTENTIAL HABITAT SUITABILITY IN BUKIT BARISAN SELATAN - Suyadi Suyadi; I Nengah Surati Jaya; Antonius B Wijanarto; Haryo Tabah Wibisono (BERITA BIOLOGI, 2012)
This study describes on development of habitat suitability for Sumatran tiger in Bukit Barisan Selatan National Park (BBSNP). In this study remotely-sensed data set were linked with tiger and it prey survey using camera trap to identify the environmental and human factors that influences the tiger's potential habitat, and to develop a spatial model as well as in BBSNP. All at once, the study showed that the potential model for estimating the tiger's potential habitat suitability could be developed using environmental and human factors. The most significant factors that influence the tiger habitat suitability in Bukit Barisan Selatan National Park are human factors such as distance to road and distance to forest edge and the environmental factor i.e. the number of tiger prey. The verification of the model shows that the model is capable to estimate the probability of the tiger presence having accuracy of approximately 78%. The model shows that there is no significant difference between the predicted data and actual data and having mean deviation less than 10%.